Comparison of Urease Inhibitors for Use in Rice Production on a Silt‐Loam Soil. Issue 1 (9th January 2015) - Rogers, Christopher W.; Norman, Richard J.; Brye, Kristofor R.; Slaton, Nathan A.; Smartt, Alden D.
Abstract : In drill‐seeded, delayed‐flood rice ( Oryza sativa L.), the large preflood application of nitrogen (N) is typically supplied as urea. Urea is susceptible to ammonia (NH3 ) volatilization loss if the flood is not established in a timely manner. Research studies investigated the effectiveness of two sources (Agrotain‐Ultra [AGR] and Arborite AG‐NT [ARB]) of the urease inhibitor N ‐( n ‐butyl) thiophosphoric triamide (NBPT) with different adhering technologies. The two sources were compared to untreated urea, in terms of preventing rice grain yield reduction attributed to N loss when urea‐N was applied at an optimal and suboptimal rate 10, 5, and 1 day prior to flooding (DPF). Sources were also compared to untreated urea in terms of urea‐N loss via NH3 volatilization. Grain yield, averaged across N source and application time, differed among N rates, where the yield from optimally N‐fertilized rice was 8208 lb/acre, suboptimal was 6692 lb/acre, and no N was 4996 lb/acre. Averaged across N sources and rates, rice fertilized 10 DPF produced a lower yield (7227 lb/acre) than urea applied 5 DPF (7673 lb/acre) or 1 DPF (7494 lb/acre), which did not differ. Yield from the two NBPT sources did not differ (7494 lb/acre and 7584 lb/acre) and were greater than untreated urea yield (7316 lb/acre). Results indicated that NH3 volatilization from urea (15%) was greater than from urea treated with either NBPT source (3%). Both sources of NBPT were similar in effectiveness and resulted in greater yields and decreased NH3 volatilization as compared to untreated urea.